Otorhinolaryngological health of women attending antenatal care clinic in a tertiary hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Physiological changes of pregnancy have a profound effect on the head and neck region; pregnant women often present with otorhinolaryngological health challenges to the obstetricians.Objective:The objective of this study is to find out the otorhinolaryngological health complaints of pregnant women at Aminu Kano Teaching Hospital (AKTH).Materials and Methods:It was a cross-sectional study conducted among consenting pregnant women at AKTH. Ethical approval was obtained from the hospital ethical committee. The questionnaire was administered among consenting pregnant women. Data obtained were analysed using the Statistical Packages for Social Sciences version 18. Qualitative data were summarised using frequencies and percentages. Fischer's exact test was used for categorical data, and theP≤ 0.05 was considered statistically significant.Results:A total of 146 pregnant women were recruited during the study. The mean age ± standard deviation was 28.57 years ± 5.796. Only 4 (2.7%) of the pregnant women were in the first trimester, while the rest were in second 47 (32.2%) and third trimester 95 (65.1%) respectively. Furthermore, few pregnant women 10 (6.8%) presented with mild hypertension, while in 136 (93.2%) of the pregnant women, the blood pressure measurements were normal. Ear itching 35 (24.0%), headache 42 (28.8%) and heartburn 55 (37.7%) were the most frequent complaints. High blood pressure was found to be statistically associated with tinnitus (P= 0.035), and high parity was also found to be associated with aural fullness (P= 0.028).Conclusion:The common otorhinolaryngological manifestations among pregnant women in this study were otomycosis, rhinitis and gastroesophageal reflux disease.